Look at Him - Starobinet︠s︡, Anna (Book collections on Project MUSE., 2020)
"Anna Starobinets's memoir Look at Him chronicles the loss of the author's unborn child to a fatal birth defect. The title refers to advice Starobinets receives in Germany when making the decision to terminate her pregnancy (the child would have suffocated at birth): better to look at one's dead child than bury the child unseen. Afterwards, Starobinets suffers from nightmares and panic attacks; the memoir describes her difficulties in finding sympathy and psychological support for herself and her family back home in Russia. The book's second half contains interviews with German medical providers experienced in treating women like Starobinets"--